Community capacity influencing community participation: Evidence from Ethiopia. (September 2022) - Gamo, Bereket Roba; Park, Duk-Byeong
Highlights: Community capacity influences community participation. Social position of respondents negatively influences their participation in the community. Respondents with community problem assessment skills were more likely to participate. Sense of community positively influences community participation. Respondents who have several social networks are more likely to participate in their community. Abstract: Community capacity and community participation have been dominant terminologies in the community development discourse recently. The two concepts also constitute a central position in the practice of community development. Our study aimed to examine the dimensions of community capacity that influence community participation of rural residents in Yirgachefe district, Ethiopia. We collected data from 360 respondents, who were all heads of households and analyzed them using descriptive statistics and hierarchical regression to determine which variables predicted higher rates of community participation. Our study finds that older people, more educated, and higher income earners were more likely to participate in their community, while the social position of respondents negatively influenced participation. Among community capacity indicators, residents' perceptions of community problem assessment skills, respondents' sense of community, and community connectedness were significant predictors of community participation. These findings suggest that expansion of educational service and vocational training to enhance capacity and initiation of strong community networking mechanisms and social activities would augment participation. Our findings also add to the limited literature pertaining to community capacity and community participation notably in the sub-Saharan region.